2007
DOI: 10.1111/j.1538-7836.2007.02373.x
|View full text |Cite
|
Sign up to set email alerts
|

The humoral response to human factor VIII in hemophilia A mice

Abstract: Summary. Background: Inhibitory antibodies (Abs) to factor VIII (FVIII inhibitors) constitute the most significant complication in the management of hemophilia A. The analysis of FVIII inhibitors is confounded by polyclonality and the size of FVIII. Objectives: The goal of this study was to dissect the polyclonal response to human FVIII in hemophilia A mice undergoing a dosage schedule that mimics human use. Methods: Splenic B-cell hybridomas were obtained following serial i.v. injections of submicrogram doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 35 publications
7
66
0
Order By: Relevance
“…However, a recent study has reported an unrestricted repertoire of anti-FVIII IgG in H-2D b FVIII-deficient mice. 8 In addition, while anti-VWF IgG have never been reported in patients treated with pdFVIII, we observed the development of VWF-specific IgG. This might be related to the sequence differences between the endogenous murine VWF and the exogenously administered human VWF (83% homology in amino acid sequences).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 60%
“…However, a recent study has reported an unrestricted repertoire of anti-FVIII IgG in H-2D b FVIII-deficient mice. 8 In addition, while anti-VWF IgG have never been reported in patients treated with pdFVIII, we observed the development of VWF-specific IgG. This might be related to the sequence differences between the endogenous murine VWF and the exogenously administered human VWF (83% homology in amino acid sequences).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 60%
“…11,29 The supernatants of hybridomas producing anti-C1 domain antibodies were collected and antibodies purified using SP Sepharose Fast Flow or Protein G agarose chromatography columns. The immunoglobulin G (IgG) isotype and subclass were determined by enzyme-linked immunosorbent assay (ELISA) using alkaline-phosphatase isotype and subclass-specific antibodies.…”
Section: Anti-fviii C1 Domain Antibody Purificationmentioning
confidence: 99%
“…7 Most inhibitor patients with congenital hemophilia A develop antibodies against the A2 and C2 domains. [8][9][10] Healey et al 11 demonstrated a predominance of anti-fVIII antibodies to the A2 and C2 domains of fVIII in a murine hemophilia A model, but antibodies to the other domains were also detected. Characterization of the structural and functional properties of anti-A2 and anti-C2 domain monoclonal antibodies (mAbs) has advanced our understanding of the epitope spectrum of anti-fVIII antibodies [12][13][14][15] and their mechanisms of inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…To study the immunogenicity of proteins used in replacement therapy, animals genetically stripped of the analogous protein are better suited because they mimic the actual patient situation. These cases have been well documented in the hemophilia model (62,63).…”
Section: Prediction Of Immunogenicitymentioning
confidence: 93%